CD4 activation of HIV fusion. - Sattentau, Q (1992)
The primary cellular receptor for the human immunodeficiency viruses type 1 (HIV-1) and type 2 (HIV-2) is the CD4 antigen. HIV infection of CD4+ cells is initiated by binding of the virus to the cell surface, via a high affinity interaction between CD4 and the HIV outer envelope glycoprotein, gp120. The development of model systems using soluble recombinant forms of CD4 (sCD4) has allowed kinetic and thermodynamic analyses of CD4 binding to gp120, and study of the post-binding events leading to virus-cell membrane fusion. It has thus been demonstrated that the affinity of sCD4 for gp120 on virions or HIV-infected cells depends on both the primary sequence and the tertiary structure of gp120 in the membrane. With cell-line adapted isolates of HIV-1, sCD4 binding induces conformational changes in gp120, leading to the complete dissociation of gp120 from the transmembrane glycoprotein, gp41, and exposing cryptic epitopes of gp41. Similar observations have been made with cell-anchored CD4; exposure of cryptic gp41 epitopes occurs at the fusion interface between clusters of CD4-expressing and HIV-infected cells. Thus, for HIV-1, CD4 induces exposure of fusogenic components of gp41 which triggers virus-cell membrane coalescence. This is termed receptor-mediated activation of fusion. With primary isolates of HIV-1 and the related lentiviruses, HIV-2 and simian immunodeficiency virus (SIV), the CD4-induced molecular rearrangements in gp120 are more subtle, implying that there is a spectrum of responses to sCD4 binding. The high-affinity binding site on CD4 for gp120 is necessary and probably sufficient for activation of HIV fusion, although other regions of CD4 may indirectly influence viral entry. There are two regions on the envelope glycoproteins which are recognized as playing a role in HIV entry: the N-terminus of gp41 and the gp120 V3 loop. The roles of these domains are discussed.